The clinic as a gendered space: an exploratory study examining men's access to and uptake of voluntary counselling and testing services (VCT) in the context of a male-friendly health facility - Faull, Maria (Aids and Society Research Unit (ASRU), 2024)
[pg 78 missing] Men in South Africa test for HIV at lower rates than do women. Investigating ways to increase men's uptake of Voluntary Counselling and Testing (VCT) services is therefore of critical importance to public health. The Site C Men's Clinic in Khayelitsha, where this study took place, is an attempt at increasing men's use of VCT. Men's views about a male-friendly space and its influence on VCT uptake had not yet been investigated in South Africa. The Men's Clinic in Khayelitsha allowed me the opportunity to interview men attending the clinic to explore their perceptions and experiences of VCT within this environment. The central aim was to explore whether men perceive the facility to be enabling in their decision to use VCT now or in the future. Furthermore, the intention of this study was to explore whether male clients perceive male health workers any differently to women staff with specific attention to confidentiality. This is closely linked to the uptake of VCT, as trust in health-workers is central to the process. The study also sought to evaluate how this male-friendly environment may contribute to normalising testing in men, which is another encouraging factor In VCT uptake. Finally, although this is a critical issue for men's health, the study aimed to investigate whether VCT services targeted at men, may benefit women's health too. The interviews were qualitative, semi-structured interviews. Being an exploratory study dealing with men's perceptions of the clinic and its services, the qualitative approach was valid. This interview approach allowed for variety in answers, but also revealed commonality, as themes emerged in response to questions. The project involved 33 qualitative interviews with men attending the clinic In Khayelitsha (including 15 men who tested at the clinic and 18 non-testers). The client interviews took place between 5 - 27th October 2007. Getting men to test for HIV is an urgent task for public health in South Africa. This study explored whether men experienced the clinic to be male-friendly and whether this influenced their attitude to testing. Most men expressed an increase in comfort and personal safety at the facility, which are valued attributes of a VCT facility. Many clients expressed greater trust in male staff, and surprisingly, trust in male patients, which contributed to their comfort at the facility. There was evidence in the interview data to suggest that male clients would contribute to normalising VCT through talking to peers about the clinic and its services. This is also likely to contribute to the greater VCT uptake in men. Testing clients seemed open to talking to their partners, having tested at the clinic. Some clients wanted to return to the facility with their partner to test. This indicates a potentially positive influence on the health of the couple. Although the clinic quantitative data indicates a slow and disappointing start for the clinic, based on the perceptions expressed by these clients, the facility is filling an important health service for men. It is likely to encourage more men to access VCT, because men feel confident in the service and staff. This is arguably in the interests of men and women's health.